2015
DOI: 10.1152/jn.00729.2014
|View full text |Cite
|
Sign up to set email alerts
|

Motor neuronal activity varies least among individuals when it matters most for behavior

Abstract: How does motor neuronal variability affect behavior? To explore this question, we quantified activity of multiple individual identified motor neurons mediating biting and swallowing in intact, behaving Aplysia californica by recording from the protractor muscle and the three nerves containing the majority of motor neurons controlling the feeding musculature. We measured multiple motor components: duration of the activity of identified motor neurons as well as their relative timing. At the same time, we measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 93 publications
4
25
0
Order By: Relevance
“…As a first step toward locating the bursts of identified motor neurons and their firing frequencies, individual spikes were detected and grouped into spike trains using manually specified window discriminators, which captured signal peaks on a given channel occurring within a given amplitude range and time window. Individual motor neurons can be identified from extracellular nerve signals in this system because of their reliable relative amplitudes and phase of activity (Morton and Chiel, 1993b;Lu et al, 2013Lu et al, , 2015McManus et al, 2014;Cullins et al, 2015b) (see Table 1). The spike amplitude of some neurons, especially B8a/b and B4/B5, can vary when these neurons activate at high frequencies due to spike collisions seen in the extracellular nerve recordings (Morton and Chiel, 1993b;Warman and Chiel, 1995), so we designed the window discriminators to account for this variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step toward locating the bursts of identified motor neurons and their firing frequencies, individual spikes were detected and grouped into spike trains using manually specified window discriminators, which captured signal peaks on a given channel occurring within a given amplitude range and time window. Individual motor neurons can be identified from extracellular nerve signals in this system because of their reliable relative amplitudes and phase of activity (Morton and Chiel, 1993b;Lu et al, 2013Lu et al, , 2015McManus et al, 2014;Cullins et al, 2015b) (see Table 1). The spike amplitude of some neurons, especially B8a/b and B4/B5, can vary when these neurons activate at high frequencies due to spike collisions seen in the extracellular nerve recordings (Morton and Chiel, 1993b;Warman and Chiel, 1995), so we designed the window discriminators to account for this variability.…”
Section: Discussionmentioning
confidence: 99%
“…The much larger forces animals generate on their own when swallowing tough foods in their natural habitat have not been measured, nor have the neural correlates of adaptation to high loads. Recent studies of the biomechanics of feeding (Neustadter et al, 2002(Neustadter et al, , 2007Kehl et al, 2019), modeling (Neustadter et al, 2002;Sutton et al, 2004a), and neural control (McManus et al, 2014;Cullins et al, 2015b;Lu et al, 2015) have provided further insights into the behavioral roles of individual neurons, suggesting that it might now be possible to relate behavior to neural activity despite the high variability.…”
Section: Introductionmentioning
confidence: 99%
“…Within these “motor equivalent” solutions, there may be some that are less desirable than others for any number of reasons, including energetics, stability, and generalizability across tasks. However, finding optimal solutions may be challenging, as muscle activation patterns have complex and nonlinear relationships to biomechanical functions (Cullins et al, 2014). …”
Section: Neuromechanical Principles Underlying Motor Module Organizationmentioning
confidence: 99%
“…In contrast, the solutions showed high variability in the “don’t care” region late in the stance phase, during which the model leg continued to move backwards but was no longer able to exert force (Beer et al, 1999). For example, distributions of motor neuron activation duration varies from one individual to another in Aplysia feeding behavior, but when motor neuron duration and timing play a critical role in a behavior such as closing its grasper to retract food, the distributions become similar across all individuals (Cullins et al, 2014). In contrast, there is high variability in the duration of motor neuron activity to close the grasper if the animal fails to grasp food, as the motor neuronal activity is no longer functionally relevant.…”
Section: Neuromechanical Principles Underlying Motor Module Organizationmentioning
confidence: 99%
“…For example, during locomotion, each step may vary within and across individuals, even when behavior is normalized by step cycle duration [13]. Our previous work demonstrated that motor components that matter for effective behavior show less individuality [14]. Is sensory feedback the mechanism for reducing individuality?…”
mentioning
confidence: 99%